Ruski film odjuge in ženski pogled - Banko, Anja (Družboslovne razprave, 2017)
The article critically reflects on Soviet cinema of the Thaw through the female gaze of Larisa Shepitko and Kira Muratova. The image and role of a woman torn between the official discourse (upheld by the state ideology) and one created in the intimacy of the home are analysed. Moreover, the article rethinks the role of feminism in the context of Russian thought, created on a specific background as imposed in the communist idea. Unlike in the West, it is based on the essentialist idea of a binary separation of differences between the sexes, which appears schizophrenic under the pressure of the state ideology. We search for these contradictory lapses in the images of the woman as created in the specific female film language of Shepitko's Wings (Krylya, 1966) and Muratova's Brief Encounters (Korotkie vstrechi, 1967) and Long Farewells (Dolgie provody, 1971).
Keywords: Ruski film; Russian motion pictures; woman; Ženske; Feminism; Feminizem; podoba ženske